Developing Android-Based Interactive Mobile Learning Software To Improve Students’ Analysis And Synthesis Abilities On Basic Electronics - Ruhimat, Toto; Rosdiana, Tata Risdian (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This research aims to improve students' analysis and synthesis abilities on electronic component learning material using the Research and Development (R&D) method. Data were obtained from tenth-grade students of the Industrial Electronic Engineering Department in Bandung Regency and analyzed using the pre-test and Post-test with normalized gain. The results showed that during the stages of limited and product operational testing, the developed product tends to improve students' analysis and synthesis abilities in basic electronic learning material with electronic component sub-materials. Therefore, Android-Based Interactive Mobile Learning has succeeded in creating new and effective ways for students to learn.